Agama Dan Krisis Iklim : Menganalisis Tentang Solidaritas Sosial Berbasis Spritualitas Di Kota Sorong, Provinsi Papua Barat Daya - Natasya Virginia Leuwol; Marcya Vanessa Glory Pical; Zeth Momot; Bentelina Rut Fiay (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2026)
The climate crisis represents a global challenge that affects not only ecological dimensions but also the social, moral, and spiritual aspects of human life. This study aims to analyze the role of religion and spirituality in fostering faith-based social solidarity in addressing the climate crisis in Sorong City, Southwest Papua Province. The research employs a library research method with a qualitative descriptive approach, drawing from books, academic journals, and relevant publications on religion, spirituality, and ecology. The findings reveal that religion plays a crucial role in shaping ecological awareness and moral responsibility toward nature as God’s creation. Spirituality acts as an inner motivation that nurtures empathy and ecological concern, while faith-based social solidarity encourages interfaith collaboration in environmental conservation efforts. In Sorong City, religious diversity serves as a valuable foundation for developing united ecological and social movements as an expression of love for the Earth. Thus, religion and spirituality function not merely as belief systems but as moral and social forces that unite humanity in responding to the climate crisis.